Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/ndt/gfu308
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylgalactosaminide α2,6-sialyltransferase II is a candidate enzyme for sialylation of galactose-deficient IgA1, the key autoantigen in IgA nephropathy

Abstract: Our data provide direct evidence that ST6GalNAc-II can sialylate GalNAc of galactose-deficient IgA1. As serum levels of galactose-deficient IgA1 with sialylated glycoforms are increased in IgAN patients, our data explain the corresponding part of the biosynthetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…O-glycans consist of N-acetylgalactosamine (GalNAc) linked with galactose (Gal; β1,3-linkage). The GalNAc-Gal disaccharide may be sialylated (linked with sialic acids) on GalNAc (α2,6-linkage), Gal (α2,3-linkage), or both [15,16,19].…”
Section: Structure Of Human Igamentioning
confidence: 99%
“…O-glycans consist of N-acetylgalactosamine (GalNAc) linked with galactose (Gal; β1,3-linkage). The GalNAc-Gal disaccharide may be sialylated (linked with sialic acids) on GalNAc (α2,6-linkage), Gal (α2,3-linkage), or both [15,16,19].…”
Section: Structure Of Human Igamentioning
confidence: 99%
“…In addition, glomerular IgA immunodeposits in patients with IgAN are enriched for Gd-IgA1 glycoforms [6,7], further supporting the role of abnormal IgA1 O-glycosylation in pathogenesis of IgAN [9,10,28,32]. Previous studies of the origin of Gd-IgA1 indicated abnormalities in the biosynthetic process in IgA1-producing cells, specifically the altered expression of genes encoding several key glycosyltransferases [12][13][14]. Recent GWAS findings showed an association of IgAN with SNPs for critical glycosyltransferase and chaperone genes, C1GALT1 and COSMC.…”
Section: Discussionmentioning
confidence: 84%
“…Enzyme activities of C1GALT1 and ST6GalNAc-II mirrored the expression of the corresponding genes. Follow-up studies indicated that some cytokines (e.g., interleukin [IL]-4 and IL-6) can alter the expression of C1GALT1, COSMC, and/or ST6GALNAC2 genes to further dysregulate activities of the encoded enzymes [12][13][14]. These findings together suggested that elevated production of Gd-IgA1 in patients with IgAN was due to an abnormal biosynthesis in IgA1-secreting cells rather than galactose removal/degradation.…”
Section: Introductionmentioning
confidence: 99%
“…GalNAc-T2 was the identified as the key enzyme initiating glycosylation of IgA1 [75]. GalNAc-T14 is another candidate GalNAc-T involved in IgA1 HR O -glycosylation [12, 76]. Attachment of GalNAc is followed by addition of Gal from UDP-Gal catalyzed by C1GalT1.…”
Section: Figmentioning
confidence: 99%